Do the Poor Benefit from Public Spending? A Look at the Evidence (The Pakistan Development Review, 2005)
This paper shows that public spending on basic services, to wit, primary and secondary education and basic health care, benefit the poor; while the non-poor are the principal beneficiaries of tertiary and education subsidies and hospital spending. The evidence also shows that expenditures on infrastructure spending tend to benefit the nonpoor disproportionately more than the poor.